Identification and Biochemical Evidence of a Medium-Chain-Length Polyhydroxyalkanoate Depolymerase in the Bdellovibrio bacteriovorus Predatory Hydrolytic Arsenal - Martínez, Virginia (American Society for Microbiology, 2012)
The obligate predator Bdellovibrio bacteriovorus HD100 shows a large set of proteases and other hydrolases as part of its hydrolytic arsenal needed for its predatory life cycle. We present genetic and biochemical evidence that open reading frame (ORF) Bd3709 of B. bacteriovorus HD100 encodes a novel medium-chain-length polyhydroxyalkanoate (mcl-PHA) depolymerase (PhaZ(Bd)). The primary structure of PhaZ(Bd) suggests that this enzyme belongs to the α/β-hydrolase fold family and has a typical serine hydrolase catalytic triad (serine-histidine-aspartic acid) in agreement with other PHA depolymerases and lipases. PhaZ(Bd) has been extracellularly produced using different hypersecretor Tol-pal mutants of Escherichia coli and Pseudomonas putida as recombinant hosts. The recombinant PhaZ(Bd) has been characterized, and its biochemical properties have been compared to those of other PHA depolymerases. The enzyme behaves as a serine hydrolase that is inhibited by phenylmethylsulfonyl fluoride. It is also affected by the reducing agent dithiothreitol and nonionic detergents like Tween 80. PhaZ(Bd) is an endoexohydrolase that cleaves both large and small PHA molecules, producing mainly dimers but also monomers and trimers. The enzyme specifically degrades mcl-PHA and is inactive toward short-chain-length polyhydroxyalkanoates (scl-PHA) like polyhydroxybutyrate (PHB). These studies shed light on the potentiality of these predators as sources of new biocatalysts, such as an mcl-PHA depolymerase, for the production of enantiopure hydroxyalkanoic acids and oligomers as building blocks for the synthesis of biobased polymers.